Stress and deformation analysis of a reinforced continuous girder bridge. (26th November 2019) - Ji, Dong-Yu; Li, Xiao-Fen
In order to study the stress and deformation of reinforced concrete continuous beam bridge, numerical simulation analysis of reinforced concrete continuous girder bridge is carried by finite element method. The results show that, the tensile stress of the bridge deck generally appears in the lower part of the span and the upper part of the support, while the compressive stress generally appears in the upper part of the span and the lower part of the support. The displacement of bridge superstructure is larger than that of substructure and soil layer, the vertical deformation of the bridge is mainly caused by the gravity of the bridge. The research results provide some references for the design and construction of continuous girder bridge.